Photographing Mexico’s Ultra-Wealthy: Daniela Rossell’s Ricas y Famosas - Gardner, Nathanial (Revista Canadiense de Estudios Hispánicos, 2021)
This paper engages with the visual strategies the photographer Daniela Rossell employed in her groundbreaking book on Mexico’s ultra-wealthy: Ricas y Famosas. This essay applies photography theory in new directions to suggest explanations for the strong public backlash that this documentary narrative provoked when it was released. To that end, an analysis of the visual narrative reveals the symbols and themes within the photo essay. It also identifies a specific narrative strategy that foregrounds a strong critique of the subject matter and important considerations connected to photography’s truth claims and how the economically advantaged have been portrayed.